Apply a TADF emitter with twist configuration for high-performance green OLEDs. (1st July 2022) - Qin, Feng; Zhang, Shaoli; Ding, Yuan; Niu, Jinghua; Lin, Yafei; Hua, Wanming; Wang, Jianyun; Ye, Jiandong; Gu, Shulin
Abstract: Due to the strong concentration quenching effect, the development of non-doped devices with excellent performance is limited. Herein, a novel thermally activated delayed fluorescence (TADF) emitter which contain Spiro[anthracene-9(10H), 9'-[9H]fluoren]-10-one (9-FAO) and 9, 9-dimethyl-9, 10-dihydroacridine (DMAC) was designed and synthesized. The compound shows TADF characteristics which can be observed by transient PL decay tests. By introducing DMAC into the para-position of the 9-FAO which has a highly twisted structure, the distance between the molecules increases to inhibit concentration quenching. The non-doped OLED device by using 2-(9, 9-dimethylacridin-10(9H)-yl)-10H-spiro[anthracene-9, 9'- fluoren]-10-one (DMTO-DMAC) as emitter achieved a superior current efficiency of 35.6 cd A −1 and maximum external quantum efficiency of 11.3% with an emission peak at 516 nm. This work demonstrates the feasibility of increasing intermolecular distance to obtain highly efficient non-doped devices.